Construction of Prochloraz-Loaded Hollow Mesoporous Silica Nanoparticles Coated with Metal–Phenolic Networks for Precise Release and Improved Biosafety of Pesticides - Liyin Shi; Qianwei Liang; Qikai Zang; Ze Lv; Xiaohan Meng; Jianguo Feng (Nanomaterials, 2022)
Currently, environmental-responsive pesticide delivery systems have become an essential way to improve the effective utilization of pesticides. In this paper, by using hollow mesoporous silica (HMS) as a nanocarrier and TA-Cu metal–phenolic networks as a capping agent, a pH-responsive controlled release nano-formulation loaded with prochloraz (Pro@HMS-TA-Cu) was constructed. The structure and properties of Pro@HMS-TA-Cu were adequately characterised and analysed. The results showed that the loading content of Pro@HMS-TA-Cu nanoparticles was about 17.7% and the Pro@HMS-TA-Cu nanoparticles exhibited significant pH-responsive properties. After a coating of the TA-Cu metal–phenolic network, the contact angle and adhesion work of Pro@HMS-TA-Cu nanoparticles on the surface of oilseed rape leaves after 360 s were 59.6° and 107.2 mJ·m−2, respectively, indicating that the prepared nanoparticles possessed excellent adhesion. In addition, the Pro@HMS-TA-Cu nanoparticles demonstrated better antifungal activity against Sclerotinia sclerotiorum and lower toxicity to zebrafish compared to prochloraz technical. Hence, the pH-responsive nanoparticles prepared with a TA-Cu metal–phenolic network as a capping agent are highly efficient and environmentally friendly, providing a new approach for the development of new pesticide delivery systems.